A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

Nonlinear and spatially heterogeneous carbon effects of three-dimensional urban expansion in China - Zilin Deng; Ziyan Luo; Linna Li; Yueting Ma; Yaqun Liu (Environmental Impact Assessment Review, 2026)

Measuring forced car ownership through the lens of spatial inequality: A multi-level analysis in China - Linna Li; Zilin Deng; Jialin Jiang; Tianyang Zhang (Journal of Transport Geography, 2026)

Dilute formic acid and alkaline oxidation relay treatment for the whole-fraction efficient gradient separation of space Arundo donax - Wenlong Xu; Xuanjie Zou; Ruotong Cui; Dameng Wang; Qilin Guo; Yanchao Shang; Jialin Zhao; Peijie Zong; Yifan Wu; Haozhe Zhang; Biao Liang; Linna Deng; et al. (Journal of Cleaner Production, 2025)

Novel anionic functionalized magnetic β-cyclodextrin composites with excellent adsorption capacity for moxifloxacin and wide pH adaptive adsorption capability for copper ion - Erming Ouyang; Linna Ye; Wenhao Zhang; Rui Zhao; Hongwei Yang; Suting Deng; Yuxiang Xiong; Xinhui Hu; Ziyue Zhou (Environmental Research, 2025)

Nonlinear relationship between urban form and transport CO2 emissions: Evidence from Chinese cities based on machine learning - Linna Li; Zilin Deng; Xiaoyan Huang (Journal of Geographical Sciences, 2024)

Paleontology Knowledge Graph for Data-Driven Discovery - Yiying Deng; Sicun Song; Junxuan Fan; Mao Luo; Le Yao; Shaochun Dong; Yukun Shi; Linna Zhang; Yue Wang; Haipeng Xu; Huiqing Xu; Yingying Zhao; et al. (Journal of Earth Science, 2024)

A high-resolution record of the late Hirnantian to Aeronian marine redox change in South China and its relationship with the record of graptolite biodiversity - Zongyuan Sun; Fangqi Zhao; Michael J. Melchin; Junxuan Fan; Bolin Zhang; Xin Jin; Zihu Zhang; Shengchao Yang; Qing Chen; Yiying Deng; Linna Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Genome-wide analysis of CtNF-YB and lipid synthesis regulation of CtNF-YB12 in Carthamus tinctorius L. - Sinan Deng; Ruinan Wang; Chenlu Tao; Lixia Li; Shuai Wang; Chang Jia; Yilin Liu; Ruo Du; Linna Du; Jing Yang (Plant Cell Reports, 2023)

Multiple parapatric pollinators have radiated across a continental fig tree displaying clinal genetic variation - Hui Yu; Enwei Tian; Linna Zheng; Xiaoxia Deng; Yufen Cheng; Lianfu Chen; Wei Wu; Wattana Tanming; Dayong Zhang; Stephen G. Compton; Finn Kjellberg (Molecular Ecology, 2019)
The ways that plant‐feeding insects have diversified are central to our understanding of terrestrial ecosystems. Obligate nursery pollination mutualisms provide highly relevant model systems of how plants and their insect associates have diversified and the over 800 species of fig trees ( Ficus ) allow comparative studies. Fig trees can have one or more pollinating fig wasp species (Agaonidae) that breed within their figs, but factors influencing their number remain to be established. In some widely distributed fig trees, the plants form populations isolated by large swathes of sea, and the different populations are pollinated by different wasp species. Other Ficus species with continuous distributions may present genetic signatures of isolation by distance, suggesting more limited pollinator dispersal, which may also facilitate pollinator speciation. We tested the hypothesis that Ficus hirta , a species for which preliminary data showed genetic isolation by distance, would support numerous pollinator species across its range. Our results show that across its range F. hirta displays clinal genetic variation and is pollinated by nine parapatric species of Valisia . This is the highest number of pollinators reported to date for any Ficus species, and it is the first demonstration of the occurrence of parapatric pollinator species on a fig host displaying continuous genetic structure. Future comparative studies across Ficus species should be able to establish the plant traits that have driven the evolution of pollinator dispersal behaviour, pollinator speciation and host plant spatial genetic structure.